Application of Mindfulness Method in Learning to Improve Concentration of Elementary School Students - Rosmiati Rosmiati; Nuryati Nuryati (Ludi Litterarri, 2024)
Learning in primary schools plays an important role in shaping students' cognitive, emotional and social abilities. One of the main challenges faced is students' lack of concentration in the learning process. Rapidly evolving digital technology exacerbates this problem, with distractions from digital devices reducing students' focus. To address this, implementing mindfulness in learning can be an effective solution. Mindfulness can improve concentration, reduce stress, and help students manage their emotions. This study aims to explore the application of mindfulness in elementary schools as an effort to improve students' concentration. A descriptive qualitative approach was used involving 5 teachers, 10 students, 5 parents, and 2 education experts as research subjects. Data were collected through interviews, observation, and documentation, and analyzed using thematic analysis. The results showed that mindfulness can improve students' focus, despite challenges such as lack of training for teachers and resistance from parents. With the right support, mindfulness can be effectively applied to support students' academic and social-emotional development in elementary school